Expresión (¬R˅P→S)&(¬R→¬S)
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
¬r⇒¬s=r∨¬s(p∨¬r)⇒s=s∨(r∧¬p)(¬r⇒¬s)∧((p∨¬r)⇒s)=r∧(s∨¬p)
r∧(s∨¬p)
Tabla de verdad
+---+---+---+--------+
| p | r | s | result |
+===+===+===+========+
| 0 | 0 | 0 | 0 |
+---+---+---+--------+
| 0 | 0 | 1 | 0 |
+---+---+---+--------+
| 0 | 1 | 0 | 1 |
+---+---+---+--------+
| 0 | 1 | 1 | 1 |
+---+---+---+--------+
| 1 | 0 | 0 | 0 |
+---+---+---+--------+
| 1 | 0 | 1 | 0 |
+---+---+---+--------+
| 1 | 1 | 0 | 0 |
+---+---+---+--------+
| 1 | 1 | 1 | 1 |
+---+---+---+--------+
(r∧s)∨(r∧¬p)
Ya está reducido a FNC
r∧(s∨¬p)
(r∧s)∨(r∧¬p)
r∧(s∨¬p)